Factors associated with the level of self-efficacy in breastfeeding women from IMSS, Tabasco - Garrido Pérez, Silvia María Guadalupe; Xala Méndez, César Alberto; Domínguez Vega, Guadalupe Montserrat (Horizonte Sanitario, 2023)
Objective: To determine the factors associated with the level of self-efficacy in lactating women from UMF No. 47, IMSS, Tabasco. Material and Methods: Observational, cross-sectional and analytical study, in a sample of 197 lactating women, who met the inclusion criteria. A sociodemographic and obstetric questionnaire designed by the researcher was applied, as well as the breastfeeding self-efficacy scale in its short form (BSES-SF), of 14 items, with Cronbach’s alpha of 0.92. The analysis included descriptive statistics, as well as inferential statistics where Pearson’s chi-square test was used. The magnitude of association was obtained, with the prevalence risks (2x2 tables), and value of p≤0.05 with Fisher’s exact test. The data were processed in the statistical program SPSS 25 and STATA 6. Results: Minimum age 17 and maximum 40, the group of 21-25 years predominated with 31.5% (X2=109.944a, gl=8, p<.001, RP 7.87, Fisher’s exact test p<0.001), free union with 46.2% (X2=71.736a, gl=6, p<.001, RP 6.51, Fisher’s exact test p<0.001), preparatory with 41.1% ( X2=18.252a, gl=6, p<.006, RP 1.51, Fisher’s exact test p<0.04), medium socioeconomic level with 52.8% (X2=38.784a, gl=4, p<.001, RP 3.42 , Fisher’s exact test p<0.001), with 2 children 35% (X2=44.647a, gl=6, p<.001, RP 4.65, Fisher’s exact test p<0.001) and if they received guidance with 94.9 % (X2=5.175a, gl=2, p=.075, RP .910, Fisher’s exact test p<0.03). Conclusions: Factors such as age, marital status, education, socioeconomic level, parity and the orientation received, were associated with the level of self-efficacy in breastfeeding, while occupation and type of delivery were not associated. Keywords: Breastfeeding; Self-efficacy; Factors.